Nuprl Lemma : req-rdiv2
∀x,y,z,u:ℝ.  (z ≠ r0 
⇒ u ≠ r0 
⇒ ((x/u) = (y/z) 
⇐⇒ (x * z) = (y * u)))
Proof
Definitions occuring in Statement : 
rdiv: (x/y)
, 
rneq: x ≠ y
, 
req: x = y
, 
rmul: a * b
, 
int-to-real: r(n)
, 
real: ℝ
, 
all: ∀x:A. B[x]
, 
iff: P 
⇐⇒ Q
, 
implies: P 
⇒ Q
, 
natural_number: $n
Definitions unfolded in proof : 
all: ∀x:A. B[x]
, 
implies: P 
⇒ Q
, 
iff: P 
⇐⇒ Q
, 
and: P ∧ Q
, 
member: t ∈ T
, 
uall: ∀[x:A]. B[x]
, 
uimplies: b supposing a
, 
prop: ℙ
, 
rev_implies: P 
⇐ Q
, 
rdiv: (x/y)
, 
uiff: uiff(P;Q)
, 
rev_uimplies: rev_uimplies(P;Q)
, 
stable: Stable{P}
, 
not: ¬A
, 
or: P ∨ Q
, 
false: False
, 
guard: {T}
Latex:
\mforall{}x,y,z,u:\mBbbR{}.    (z  \mneq{}  r0  {}\mRightarrow{}  u  \mneq{}  r0  {}\mRightarrow{}  ((x/u)  =  (y/z)  \mLeftarrow{}{}\mRightarrow{}  (x  *  z)  =  (y  *  u)))
Date html generated:
2020_05_20-AM-11_00_11
Last ObjectModification:
2020_01_06-PM-00_26_43
Theory : reals
Home
Index